Fasting Ramadan During COVID-19 Pandemic: Immunomodulatory Effect - Abunada, Taghreed; Abunada, Hanan; Zayed, Hatem (Frontiers in Nutrition, 2020)
As of April 24, 2020, more than 1. 6 billion Muslims observe the holy fasting month of Ramadan worldwide. The safety of fasting of healthy adult Muslims during the COVID-19 era is debatable. In this perspective, we discuss the available scientific evidence of the advantages of fasting against COVID-19.